STUDI TINGKAT KEPUASAN KARYAWAN DAN NASABAH TERHADAP PELAYANAN BMT - Ibnu Syaichul Islam; Supriady Rusli; Naddin Naddin (JEP (Jurnal Ekonomi Pembangunan), 2021)
This study aims to find out how the role of Amanah Kendari BMT to increase employee satisfaction and cusmtomer. The data used in this study are primary data and secondary data that is, through interviews and documentation sourced from respondents’ responses regarding the role of BMT Amanah’s productive financing of member welfare in terms of Islamic law. The results of this study indicate that there is a positive and significant effect on service quality on the saticfaction of employees of BMT Amanah Kendari, in the level of saticfaction customers have been satisfied with the service they received at BMT Amanah. Seen from the answers of respondents (employees) on questions that researchers describe. Which is there are several factors, namely the factor of working together, the factor of personal service, the factor of providing information when receiving the latest service and the explanation factor of the information that the customer wants to know.